106k views
5 votes
Factor -4x + 24 - 4x^2

User Starbax
by
5.5k points

1 Answer

5 votes

Answer:

- 4(x + 3)(x - 2)

Explanation:

Given

- 4x + 24 - 4x² ← rewrite in standard form, that is

- 4x² - 4x + 24 ← factor out - 4 from each term

= - 4(x² + x - 6) ← factorise the quadratic

Consider the factors of the constant term (- 6) which sum to give the coefficient of the x- term (+ 1)

The factors are + 3 and - 2, since

3 × - 2 = - 6 and 3 - 2 = + 1, hence

x² + x - 6 = (x + 3)(x - 2), and

4x² - 4x + 24 = - 4(x + 3)(x - 2)

User Drew Olson
by
6.1k points